Human Variability in Carboxylesterases and carboxylesterase-related Uncertainty Factors for Chemical Risk Assessment. (10th October 2021) - Di Consiglio, E.; Darney, K.; Buratti, F.M.; Turco, L.; Vichi, S.; Testai, E.; Lautz, L.S.; Dorne, J.L.C.M.
Highlights: Extensive literature search of human kinetic parameters and enzyme activities for in vivo CES-1 and CES-2 probe substrates. Hierarchical Bayesian meta-analysis to quantify inter-individual differences. Human variability in CES ranges from 30-55% for CES1 and CES2 across probe substrates. Abstract: Carboxylesterases (CES) are an important class of enzymes involved in the hydrolysis of a range of chemicals and show large inter-individual variability in vitro . An extensive literature search was performed to identify in vivo probe substrates for CES1 and CES2 together with their protein content and enzymatic activity. Human pharmacokinetic (PK) data on Cmax, clearance, and AUC were extracted from 89 publications and Bayesian meta-analysis was performed using a hierarchical model to derive CES-related variability distributions and related uncertainty factors (UF). The CES-related variability indicated that 97.5% of healthy adults are covered by the kinetic default UF (3.16), except for clopidogrel and dabigatran etexilate. Clopidogrel is metabolised for a small amount by the polymorphic CYP2C19, which can have an impact on the overall pharmacokinetics, while the variability seen for dabigatran etexilate might be due to differences in the absorption, since this can be influenced by food intake. The overall CES-related variability was moderate to high in vivo (<CV 50%), which might be due to possible polymorphism in the enzyme but also to the small sample size available per chemical. The presented CES-related variability can be used in combination with in vitro data to derive pathway-specific distributions.